(untitled) (Educational Dimension, 2021)
The article is devoted to the analysis of foreign experience in determining the criteria for assessing the effectiveness of scientific and pedagogical research. Thus, the problems of qualified analysis of the source base and reproducibility of research, the use of formal scientometric indicators, altmetric approaches, and digital libraries are considered. Another conclusion of authors is to ensure the reliability of the results, and, accordingly, for higher evaluation indicators of research performance, peer-reviewed publications indexed in scientometric databases should be used as primary sources. At the same time, the implementation of a digital identifier (first of all DOI), the provision of open data of research results, and the availability of copies in digital institutional repositories also contribute to higher performance indicators of scientific and pedagogical research. Despite the implementation of various new scientometric indicators, still the most used is the citation (H-index). Altmetric indicators receive data from social networks. Articles are published in them have a faster release of the results. But many scientists still doubt whether there is a direct relationship between the publication impact according to the classical and altmetric approaches. The main reason for this is the authors’ ability to artificially influence some impact indicators.